Composite biomarker panel for prediction of severity and diagnosis of acute GVHD with T-cell-depleted allogeneic stem cell transplants—single centre pilot study. Issue 10 (27th April 2017) - Min, San San; Mehra, Varun; Clay, Jennifer; Cross, Gemma F; Douiri, Abdel; Dew, Tracy; Basu, Tanya N; Potter, Victoria; Ceesay, M Mansour; Pagliuca, Antonio; Sherwood, Roy A; Vincent, Royce P
Abstract : Aims: Acute graft-versus-host disease (aGVHD) is a leading cause of morbidity and mortality following allogeneic haematopoietic stem cell transplantation (HSCT). The aim of this study was to evaluate the clinical utility of a composite biomarker panel to help identify individuals at risk of developing aGVHD, and to help predict and differentiate between severity of aGVHD following T-cell-depleted allogeneic HSCT. Methods: We retrospectively analysed our cohort of biopsy confirmed patients with aGVHD, who underwent T-cell-depleted HSCT and matched them with negative controls without any evidence of aGVHD. Post-transplant serum samples on days 0 and 7 and at onset of aGVHD were analysed for elafin, regenerating islet-derived 3-α, soluble tumour necrosis factor receptor-1, soluble interleukin-2 receptor-α and hepatocyte growth factor. Biomarker data were combined as composite panels A–F (table 2) using logistic regression analysis. Receiver operating characteristic analysis was performed to study sensitivity and specificity of the composite panels. Results: Our composite biomarker panels significantly differentiated between aGVHD and no GVHD patients at time of onset (panel E) and reliably predicted severity of GVHD grades at days 0 and 7 post-transplant (panels B and D). The area under the curve for the composite panel at time of onset was 0.65 with specificity, sensitivity, positive and negative predictive values of 100%, 55.6%, 100% and 78.9%, respectively ( p=0.03 ). Conclusions: This pilot data support the usefulness of these composite biomarker panels in the prediction of severity and diagnosis of aGVHD in patients undergoing T-cell-depleted reduced intensity allogeneic HSCT.